Electromagnetic phenomena in cosmical physics - Lehnert, B. (Bo) 1926- (International Astronomical Union Symposium, 2016)
This book contains papers from symposium number 6, organised by the International Astronomical Union and held on 27th-28th and 30th-31st August 1956.